Improve the productivity of rubber bushings in a rubber moulding company by applying the Lean Principle - Gopi Simathari (2021)
The rubber moulding manufacturing businesses are facing problems to fulfil the customer requirements and stay competitive with the global players in terms of cost, quality and services. Some of the notable rubber moulding industries are unable to meet the customer requirements in the aspect of delivery time and demand. One of the reasons why most of the rubber moulding manufacturing companies are still unable to implement lean manufacturing systems due to a lack of knowledge and information. The drive for yearly cost savings from automotive customers has driven suppliers to research ways to improve production efficiency and raise production. Companies are continuously searching for new instruments to optimise manufacturing processes, which provide considerable increases in productivity, savings and customer satisfaction. This study aims to reduce waste and increase the productivity of the rubber moulding manufacturing process by using the Lean principles, which can help identify waste from information flow, material flow, and process flow. In this study, lean principles with the support of the Ishikawa Diagram were able to find the highest cessation process that contributed to non-value-added activities in rubber production. Finishing processes, which have the highest process steps selected for improvement study. The study shows that productivity increased by implementing the cellular manufacturing principles. A complete process step can be reduced from 22.5 hours to 0.5 hours in the Finishing process. (Abstract by author)